Maps and mapping. ([Australia] : [publisher not identified], 1931)
Includes articles from the period 1931 to 1989. There are historical features, articles on historic maps, including map of Tasman's voyage in 1642, and Dieppe maps by Colinbridge, and articles on map makers.
Newspaper cuttings from the Australian press clippings collection covering geographic places, including Australian states, towns and geographical features. Content covers the time period from 1931 to 1989.
Keywords: Cartography -- Australia -- History; Cartographers -- Australia; Maps; Australian